Pengaruh Daya Tarik Live Tiktok, Review Produk, dan Diskon Terhadap Minat Beli Pelanggan - Niam Rahma Isnaini; Imronudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the extent to which live streaming sales, product reviews, and promotional discounts influence consumer purchase interest on the TikTok e-commerce platform. A quantitative research design was employed, utilizing an online questionnaire to gather data. The participants consisted of 152 respondents who are active TikTok users with prior experience shopping through its live shopping feature. The collected data were analyzed using Structural Equation Modeling (SEM) through the SmartPLS application. The analysis revealed that discount offerings have a statistically significant and positive impact on consumer purchase interest. In contrast, live streaming selling and product reviews did not demonstrate a meaningful influence. These findings suggest that within the TikTok Shop environment, price incentives play a dominant role in driving purchasing behavior, while the influence of live streams and customer reviews may require further strategic enhancement in terms of presentation and communication effectiveness. This research contributes to the theoretical framework of digital consumer behavior and provides practical insights for businesses aiming to refine their social media-based marketing strategies.